2021
DOI: 10.1186/s12888-021-03197-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of psychosocial distress among seafarers during COVID-19 pandemic

Abstract: Background In the context of growing concerns about seafarers’ mental health during the COVID-19 pandemic, this study aimed to assess the prevalence and associated factors of psychosocial distress among seafarers of ocean-going vessels during the current health emergency. Methods This cross-sectional study was conducted among 470 multinational seafarers working on two oil tanker international shipping companies. Psychosocial distress was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 22 publications
3
48
0
1
Order By: Relevance
“…Previous cross-sectional studies on seafarers’ mental health during the COVID-19 pandemic ( Baygi et al, 2021 , Qin et al, 2021 ) suggested that the pandemic might have led to an increase in mental health problems. However, due to the cross-sectional design, these studies could not account for the pre-pandemic levels of seafarers’ depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous cross-sectional studies on seafarers’ mental health during the COVID-19 pandemic ( Baygi et al, 2021 , Qin et al, 2021 ) suggested that the pandemic might have led to an increase in mental health problems. However, due to the cross-sectional design, these studies could not account for the pre-pandemic levels of seafarers’ depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence is sparse and less systematic, but points toward negative impacts of the current crisis on seafarers’ mental health and well-being. Baygi et al (2021) , in a cross-sectional study of 439 international seafarers, found a high prevalence of psychiatric disorders, depression and anxiety. Moreover, length of time on board was associated with increased risk of depression.…”
Section: Seafarers’ Mental Health and The Impact Of The Covid-19 Pandemicmentioning
confidence: 98%
See 3 more Smart Citations